Application of Symposium Learning Method to Enhance High School Students' Critical Disposition and Critical Thinking Skills in Addressing Socioscientific Issues in Biology - Ririn Mardiana Saputri; AA Sukarso; Prapti Sedijani; Agus Ramdani; Rangga Alif Faresta (Postgraduate Program, University of Mataram, 2024)
This study explores the effectiveness of the Symposium Learning Method in enhancing critical disposition and critical thinking skills among high school students in the context of biology education. Employing a quasi-experimental design, the research compares the outcomes of students instructed using the Symposium Learning Method with those taught through conventional methods. Pre-test and post-test assessments were conducted to evaluate students' critical disposition and critical thinking skills. The findings reveal a significant improvement in both critical disposition and critical thinking skills among students exposed to the Symposium Learning Method. This underscores the method's efficacy in promoting active participation, collaborative learning, and deeper engagement with course material. The study emphasizes the importance of innovative teaching approaches in nurturing critical thinking skills essential for addressing complex societal issues in biology education.